Border Terriers under primary veterinary care in England: demography and disorders. Issue 1 (December 2017) - O'Neill, Dan; Darwent, Elisabeth; Church, David; Brodbelt, Dave
Abstract Background The Border Terrier is a working terrier type that is generally considered to be a relatively healthy and hardy breed. This study aimed to characterise the demography and common disorders of Border Terriers receiving veterinary care in England using de-identified electronic patient record data within the VetCompass™ Programme. Results Annual birth proportion for Border Terriers showed a decreasing trend from 1.46% in 2005 to 0.78% in 2014. The median adult bodyweight for males (10.9 kg, IQR: 9.6–12.3, range: 6.3–25.0) was higher than for females (9.1 kg, IQR: 8.2–10.3, range: 5.2–21.6) (P  < 0.001). The median longevity was 12.7 years (IQR 9.3–14.3, range 1.0–17.5). The most prevalent fine-level disorders recorded were periodontal disease (17.63%, 95% CI: 15.62–19.79), overweight/obesity (7.01%, 95% CI: 5.69–8.52) and otitis externa (6.71%, 95% CI: 5.42–8.19). The most prevalent grouped-level precision disorders were dental disorder (18.54%, 95% CI: 16.48–20.74), enteropathy (11.68%, 95% CI: 10.00–13.53), and skin disorder (10.17%, 95% CI: 8.60–11.93). Syndromic analysis showed that the most prevalent body locations affected were the head-and-neck (37.75%, 95% CI: 35.14–40.43), abdomen (18.61%, 95% CI: 16.55–20.81) and limb (11.53%, 95% CI: 9.86–13.37). At least one organ system was affected in 834 (62.85%) Border Terriers. The most prevalent organ systems affected were the digestive (32.03%, 95% CI: 29.52–34.61), integument (26.68%, 95% CI: 24.31–29.14), connective/soft tissue (11.15%, 95% CI: 9.51–12.97) and auditory (9.87%, 95% CI: 8.32–11.60). At least one affected pathophysiological process was described in 881 (66.39%) Border Terriers. The most prevalent pathophysiologic processes recorded were inflammation (31.65%, 95% CI: 29.15–34.23), nutritional (9.04%, 95% CI: 7.55–10.72), mass/swelling (8.89%, 95% CI: 7.42–10.55), traumatic (7.99%, 95% CI: 6.59–9.58) and infectious (7.76%, 95% CI: 6.38–9.33). Conclusions This study documented a trend towards reducing ownership and relatively long-livedness in the Border Terrier. The most common disorders were periodontal disease, overweight/obesity and otitis externa. Predisposition to dental and neurological disease was suggested. These results can provide a comprehensive evidence resource to support breed-based health plans that can contribute positively to reforms to improve health and welfare within the breed.